2019
DOI: 10.1021/acscatal.9b00650
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and Kinetics of Methylating C6–C12 Methylbenzenes with Methanol and Dimethyl Ether in H-MFI Zeolites

Abstract: This study uses periodic density functional theory (DFT) to determine the reaction mechanism and effects of reactant size for all 20 arene (C6-C12) methylation reactions using CH3OH and CH3OCH3 as methylating agents in H-MFI zeolites. Reactant, product, and transition state structures were manually generated, optimized, and then systematically reoriented and reoptimized to sufficiently sample the potential energy surface and thus identify global minima and the most stable transition states which interconnect t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
77
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 51 publications
(88 citation statements)
references
References 88 publications
11
77
0
Order By: Relevance
“…MFI contains straight and sinusoidal channels that intersect to form the channel intersection, where T11 is situated, and the three accessible O-sites of T11 reside in the straight channel (O14) or bridge straight channel and channel intersection (O16 and O25). This work, and previous work, 59 have demonstrated that the straight channel of MFI offers confinement for smaller transition states, such as those associated with aliphatic hydrogenation. Conversely, the O-sites of CHA each have different chemical environments: O1 bridges a 6 membered-ring (6-MR) and two 4-MRs, O2 spans two 8-MRs, O3 spans the 6-MR and 8-MR, and O4 spans the 8-MR and 4-MR (Fig.…”
Section: Hydrogenation In H-chasupporting
confidence: 70%
See 3 more Smart Citations
“…MFI contains straight and sinusoidal channels that intersect to form the channel intersection, where T11 is situated, and the three accessible O-sites of T11 reside in the straight channel (O14) or bridge straight channel and channel intersection (O16 and O25). This work, and previous work, 59 have demonstrated that the straight channel of MFI offers confinement for smaller transition states, such as those associated with aliphatic hydrogenation. Conversely, the O-sites of CHA each have different chemical environments: O1 bridges a 6 membered-ring (6-MR) and two 4-MRs, O2 spans two 8-MRs, O3 spans the 6-MR and 8-MR, and O4 spans the 8-MR and 4-MR (Fig.…”
Section: Hydrogenation In H-chasupporting
confidence: 70%
“…All DFT-optimized reactant, product, and transition states were modeled at all possible O-sites and O-site pairs (if the species interacted with a pair of O atoms) associated with T11 of MFI and T1 of CHA. Furthermore, all structures were systematically reoriented (Section 2.2), 59 to increase the likelihood that global minima and optimum transition state structures were obtained via static (non-dynamic) DFT calculations.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…H‐ZSM‐5, which is widely used for the alkylation of benzene due to its high activity and selectivity, was found to be less effective for the formation of toluene and xylenes as compared to H‐MOR in this study. Although yields of methylated products are low, it is worth mentioning that a relatively large amount of light alkanes (C 2 −C 4 ), which are considered as valuable products were detected when H‐CHA zeolite was used.…”
Section: Figurementioning
confidence: 73%